2021
DOI: 10.1093/rheumatology/keab816
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland swelling in primary Sjögren’s syndrome: activity and other sialadenosis causes

Abstract: Objective To assess the prevalence of parotid gland swelling (PGS) and its association with features of SS and other causes of sialadenosis in a Latin-American cohort of primary SS. Methods We included 668 patients from Argentina, Brazil, Mexico and Paraguay. We retrospectively registered demographics, disease duration, oral/ocular symptoms, serology and scored the basal ESSDAI. We defined PGS as a recurrent or persistent inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The ablation or reduced function of this gland may be observed in patients undergoing treatment for oral or head and neck cancers, particularly those treated with radiotherapy [ 138 , 139 ]. In patients with Sjögren’s syndrome, an autoimmune disease primarily affecting the salivary and lacrimal glands, dysfunction or damage to these glands can lead to reduced saliva and tear production [ 140 ]. Damage to the function of the salivary glands can occur in patients treated with antineoplastic drugs, including cyclophosphamide [ 141 ] and 5-fluorouracil [ 36 ], or with antibiotics, such as metronidazole [ 142 ], or analgesic drugs, such as tramadol [ 143 ].…”
Section: Agents Impairing the Enterosalivary Cycle Of Nitratementioning
confidence: 99%
“…The ablation or reduced function of this gland may be observed in patients undergoing treatment for oral or head and neck cancers, particularly those treated with radiotherapy [ 138 , 139 ]. In patients with Sjögren’s syndrome, an autoimmune disease primarily affecting the salivary and lacrimal glands, dysfunction or damage to these glands can lead to reduced saliva and tear production [ 140 ]. Damage to the function of the salivary glands can occur in patients treated with antineoplastic drugs, including cyclophosphamide [ 141 ] and 5-fluorouracil [ 36 ], or with antibiotics, such as metronidazole [ 142 ], or analgesic drugs, such as tramadol [ 143 ].…”
Section: Agents Impairing the Enterosalivary Cycle Of Nitratementioning
confidence: 99%
“…With respect to alcohol intake, patients with SS were less likely to consume alcohol after adjusting for age, sex and education in comparison with the general population (21), suggesting a similar pattern to that observed for smoking (oral discomfort from the intake of alcohol may underlie the lower prevalence in prevalent cases). Alcohol consumption should also be considered in patients already diagnosed with SS who develop parotid swelling during the follow-up, since a recent study (22) has reported that alcohol intake may be associated with an increased risk of parotid swelling. Regardless of the potential "protective" effects of tobacco and alcohol in SS, their negative effects in global health are undeniable and both should be avoided in patients with a suspected disease and in those already diagnosed with SS.…”
Section: Myth Smoking and Alcohol Intake May Enhance The Risk Of Sjög...mentioning
confidence: 99%